Interpretation of fast-ion signals during beam modulation experiments. (22nd July 2016) - Heidbrink, W.W.; Collins, C.S.; Stagner, L.; Zhu, Y.B.; Petty, C.C.; Van Zeeland, M.A.
Abstract: Fast-ion signals produced by a modulated neutral beam are used to infer fast-ion transport. The measured quantity is the divergence of perturbed fast-ion flux from the phase-space volume measured by the diagnostic, ∇ ⋅ Γ ∼ . Since velocity-space transport often contributes to this divergence, the phase-space sensitivity of the diagnostic (or 'weight function') plays a crucial role in the interpretation of the signal. The source and sink make major contributions to the signal but their effects are accurately modelled by calculations that employ an exponential decay term for the sink. Recommendations for optimal design of a fast-ion transport experiment are given, illustrated by results from DIII-D measurements of fast-ion transport by Alfvén eigenmodes. The signal-to-noise ratio of the diagnostic, systematic uncertainties in the modeling of the source and sink, and the non-linearity of the perturbation all contribute to the error in ∇ ⋅ Γ ∼ .